Comparison of Methodical Approaches to Environmental Risk Assessment - VOLKOVA, Elena E.; KUZMIN, Evgeny A. (Journal of Environmental Management and Tourism, 2017)
Environmental risks, their assessment and risk management techniques make a range of relevant research in the field of environmental protection. The extent of prior research on the problem does not underplay importance of a regular review of accents of the problem and approach improvements. The article makes more specific the content of such concepts, as the environmental safety and compliance and the environmental risk. It also presents threat development factors related to a change in the environment. Procedures to risk assessment for the environment exposed to pollutants are also presented. Piloted approaches make it possible to make a conclusion of procedures quality, causes for differences between level values of the risk depending on a research object. To develop the integrated concept, constituent components of the environment as homogeneous subsystems are discussed. The article provides the algorithm for the environmental risk analysis. Findings precondition the environmental risk management strategy focused on a systemic effect of regulatory measures.